The Effective of Pressure and Sintering Temperature for Hardness Characteristics of Shape Memory Alloy by Using Taguchi Technique (Journal of Engineering, 2016)
This paper presents the Taguchi approach for optimization of hardness for  shape memory alloy (Cu-Al-Ni) . The influence of  powder metallurgy parameters on hardness has been investigated. Taguchi technique and ANOVA were used for analysis. Nine experimental runs based on Taguchi’s L9 orthogonal array were performed (OA),for two parameters was study (Pressure and sintering temperature) for three different levels (300 ,500 and 700) MPa ,(700 ,800 and  900)oC respectively . Main effect, signal-to-noise (S/N) ratio was study, and analysis of variance (ANOVA) using  to investigate the micro-hardness characteristics of the shape memory alloy .after application the result of study shown the height hardness at the level 2 of pressure and level 1 of temperature  (A2B1) by taguchi technique at magnitude value 500MPa and 700 ºC. The best  effective factor at ANOVA has pressure 36.39%. the interaction given the best pressure 500 MPa and Temperature 800 ºC.